2005
DOI: 10.1016/j.jtcvs.2004.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral malperfusion in acute type A dissection: Direct innominate artery cannulation

Abstract: with a liposarcoma are symptomatic and that 15% have an asymptomatic liposarcoma discovered on a routine chest radiograph. Liposarcomas are usually large. The cases reported by Klimstra and associates 3 ranged from 6 to 40 cm, with a mean weight of 1500 g. Enzinger and Weiss 4 divided liposarcomas into the following 5 major morphologic subtypes: well differentiated, myxoid, round cell, dedifferentiated, and pleomorphic. Myxoid liposarcomas account for 40% to 50% of these tumors. Welldifferentiated liposarcomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 4 publications
1
12
1
1
Order By: Relevance
“…It was concluded that monitoring of regional cerebral tissue oxygen saturation using NIRS during SACP allows detection of clinically important cerebral desaturations and can help predict perioperative neurological sequelae. 59 There have also been a number of case reports of aortic arch surgery in which cerebral oximetry has been shown to detect cerebral hypoperfusion from a variety of factors including ascending aortic dissection with occlusion of carotid lumen, 33 intraoperative thrombosis of a common carotid graft, 69 kinking or obstruction of perfusion cannula during SACP, 67 or due to diminished Blalock -Taussig shunt flow after paediatric cardiac surgery. 65…”
Section: Coronary Artery Bypass Surgerymentioning
confidence: 99%
“…It was concluded that monitoring of regional cerebral tissue oxygen saturation using NIRS during SACP allows detection of clinically important cerebral desaturations and can help predict perioperative neurological sequelae. 59 There have also been a number of case reports of aortic arch surgery in which cerebral oximetry has been shown to detect cerebral hypoperfusion from a variety of factors including ascending aortic dissection with occlusion of carotid lumen, 33 intraoperative thrombosis of a common carotid graft, 69 kinking or obstruction of perfusion cannula during SACP, 67 or due to diminished Blalock -Taussig shunt flow after paediatric cardiac surgery. 65…”
Section: Coronary Artery Bypass Surgerymentioning
confidence: 99%
“…In small series, combined RAxA/ScA and FemA cannulation have been used to prevent malperfusion with encouraging outcomes (194). Carotid and innominate artery cannulation to avoid malperfusion have also been used by some authors (195)(196)(197)198), and occasionally unique perfusion solutions have been generated to combat intraoperative malperfusion (199).…”
Section: The Aims and Objectives Of Ataad Surgerymentioning
confidence: 99%
“…Tissue oximetry may provide information regarding oxygenation from potentially ischaemic tissues. Its clinical utility has already been demonstrated in a wide variety of clinical settings including monitoring of tissue flaps after surgery, detecting cerebral vasospasm, cerebral monitoring intraoperatively for cardiac surgery and in detecting silent cerebral ischaemia in a number of different settings . There is a growing body of research exploring the utility of NIRS cerebral oximetry in the monitoring of neurotrauma patients, incorporating not just oximetry values, but also indices derived from total haemoglobin measurements and NIRS‐derived values relying on the absorption of light by cytochromes to provide information regarding the mitochondrial redox state of monitored tissues …”
Section: Discussionmentioning
confidence: 99%